Adamantane-Monoterpenoid Conjugates Linked via Heterocyclic Linkers Enhance the Cytotoxic Effect of Topotecan - Munkuev, Aldar A.; Dyrkheeva, Nadezhda S.; Kornienko, Tatyana E.; Ilina, Ekaterina S.; Ivankin, Dmitry I.; Suslov, Evgeniy V.; Korchagina, Dina V.; Gatilov, Yuriy V.; Zakharenko, Alexandra L.; Malakhova, Anastasia A.; Reynisson, Jóhannes; Volcho, Konstantin P.; et al. (Molecules (Basel, Switzerland), 2022)
Inhibiting tyrosyl-DNA phosphodiesterase 1 (TDP1) is a promising strategy for increasing the effectiveness of existing antitumor therapy since it can remove the DNA lesions caused by anticancer drugs, which form covalent complexes with topoisomerase 1 (TOP1). Here, new adamantane–monoterpene conjugates with a 1,2,4-triazole or 1,3,4-thiadiazole linker core were synthesized, where (+)-and (−)-campholenic and (+)-camphor derivatives were used as monoterpene fragments. The campholenic derivatives 14a–14b and 15a–b showed activity against TDP1 at a low micromolar range with IC50 ~5–6 μM, whereas camphor-containing compounds 16 and 17 were ineffective. Surprisingly, all the compounds synthesized demonstrated a clear synergy with topotecan, a TOP1 poison, regardless of their ability to inhibit TDP1. These findings imply that different pathways of enhancing topotecan toxicity other than the inhibition of TDP1 can be realized.